The development and intersection of highland-coastal scale frames: a case study of water governance in central Peru. Issue 4 (4th July 2019) - Grainger, Sam; Hommes, Lena; Karpouzoglou, Timos; Perez, Katya; Buytaert, Wouter; Dewulf, Art
ABSTRACT: Scale framing makes an important difference to how complex environmental policy issues are defined and understood by different groups of actors. Increasing urban water demand and uncertain future climatic conditions in the Andes present major water governance challenges for the coastal regions of Peru. An understudied dimension of Peruvian water governance is how scale framing shapes the way problems are defined, and solutions are pursued. Here, we aim to strengthen the understanding of scale framing as it relates to highland-coastal interactions in central Peru between 2004 and 2015. By analysing this period of significant water governance reforms, we identify five prominent water-related frame dimensions and three differently scaled policy storylines and reveal how they developed and intersected over time. The storylines, supported by particular visualisations, either foreground 'urbanshed'-level investment in water supply infrastructure, community-level cultural restoration for improved local agricultural production, or nationwide watershed-level financial mechanisms for highland ecosystem conservation. Our study shows how the intersection of these storylines at different moments during the policy process often had a strengthening effect, creating a coalition of actors who were then able to generate sufficient momentum and support within the Peruvian government for the implementation of conservation-based watershed investments.